Weaving oral health provider perspectives to guide future dental therapy advocacy and implementation efforts - Amanda J. Llaneza; Amanda J. Llaneza; Kara A. Stone; Julie Seward (Frontiers in Public Health)
IntroductionAmerican Indian and Alaska Native (AI/AN) communities in the United States (U.S.) face greater oral healthcare inequities than other groups in the country. A solution to improving oral healthcare access for American Indian and Alaska Native communities in the United States is the integration of dental therapists (DT). However, it has been met with opposition. The goal of this study was to explore oral health provider engagement and perspectives of DT implementation in local communities.MethodsEngagement related to DT from the dental provider perspective from the ADTA conference's attendees were analyzed via optional, electronic post-conference surveys. Descriptive statistics were utilized to report the position type of attendees, years of experience in the role, incorporation of clinical courses for DT scope of practice, and clinic management and administration for their patients. Surveys included two open-ended questions inquiring about personal objectives and comments and suggestions regarding the conference overall. From attendee's open-ended statements on objectives for attending this conference, key patterns were described.ResultsOne hundred people nationwide attended the conference. Of these attendees, 56% completed the post-conference survey evaluation. Among the respondents, 25% identified as dentists, 23% identified as dental hygienists, 46% identified as dental therapists, 6% identified as other oral health workforce members (i.e., dental assistant and/or Tribal oral health coordinator). The majority felt the strategies covered related to DT could be incorporated regardless of the type of workforce position. Fifty-seven percent of dentists felt it would be easy or very easy to implement strategies from the conference, and 75% of dental hygienists and other oral health workforce members felt it was easy or very easy to implement strategies from the conference. Education, advocacy, and networking were identified as the main objectives for attending the conference.DiscussionThe conference platform encouraged dissenting viewpoints to contribute to academic and policy debates to ultimately provide broader access to oral healthcare through a comprehensive team approach. There was strong support across positions to advocate for and expand DT to the lower 48 states of the U.S., particularly in areas with underserved communities. Additionally, most providers felt this could be done with ease and no providers indicated opposition in open-ended remarks. Collaborative efforts among policymakers, dental associations, educational institutions, and community advocates can create a pathway for the successful integration of dental therapists into the healthcare system.